Automated Referral to Cardiac Rehabilitation following Coronary Artery Bypass Grafting is associated with limited improvements in program completion: a large cohort study. (2018) - Liu, Hongwei; Wilton, Stephen; Southern, Danielle; Knudtson, Merril; Maitland, Andrew; Hauer, Trina; Arena, Ross; Stone, James; Aggarwal, Sandeep; Martin, Billie-Jean
No abstract available